HUBUNGAN LAMA MENDERITA DIABETES MELITUS DENGAN DERAJAT RETINOPATI DIABETIK DI RUMAH SAKIT MATA SMEC MEDAN KLINIK EKSEKUTIF - KESUMA, TRI WIDYANTI (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2024)
ABSTRACT Diabetic Retinopathy is an important long-standing complication of Diabetes Mellitus. It is caused by high incidence and it’s worse prognosis i.e actuity visual loss such as blindness.The objective of the study is to find the relation duration endure of diabetic to the severity of Diabetic Retinopathy at Rs Mata SMEC Medan Klinik Eksekutif. The study involved 51 patients were recorded as a patient in hospital SMEC Eye Clinic Medan Medan. Analyzed using chi-squar.The results showed that there was a significant relationship duration endure of diabetic with the degree of diabetic retinopathy, with a value of p = 0.002 (p> 0.05). This means that the longer a person suffering from diabetes melitus is increasingly at risk of increasing the degree of diabetic retinopathy. Keywords : duration of diabetic, degree of diabetic retinopathy.